Identifikasi Kemampuan Literasi Matematika Ditinjau Dari Perspektif Kecerdasan Logis Matematis - Nursia Manu Allo; Munir Yusuf; Dwi Risky Arifanti; Winayati Naflatunnisa; M Syaifullah (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
Abstract:Mathematical literacy skills and mathematical logical intelligence are essential things that students must have to be able to use mathematics in everyday life. This study aims to identify mathematical literacy skills from the perspective of logical-mathematical intelligence of junior high school students in Towuti, East Luwu. This type of research is descriptive qualitative with data collection techniques for mathematical logical intelligence tests and tests of mathematical literacy skills and interview guidelines. The indicators used adopt indicators developed by Stecey and Turner. The research subjects used were three categories of students from class VIII room 2 who had high, medium, and low mathematical logical intelligence. The results showed that students with high mathematical logical intelligence were able to identify all indicators of mathematical literacy ability so that they had high mathematical literacy skills. It is different for students with moderate and low logical intelligence, who have low and high literacy abilities. The results of this identification are still possible to continue by an analytical study. Abstrak:Kemampuan literasi matematika dan kecerdasan logis matematis merupakan hal yang penting dimiliki siswa agar mampu menggunakan matematika dalam kehidupan sehari-hari. Penelitian ini bertujuan mengidentifikasi kemampuan literasi matematika ditinjau dari perspektif kecerdasan logis matematis siswa tingkat SMP di Towuti Kabupaten Luwu Timur. Penelitian ini bersifat kualitatif deskriptif dengan instrumen tes kecerdasan logis matematis, tes kemampuan literasi matematika, dan pedoman wawancara. Indikator yang digunakan mengadopsi teori Stecey dan Turner. Subjek penelitian adalah siswa dari kelas VIII ruangan 2 dengan kecerdasan logis matematis tinggi, sedang dan rendah. Hasil penelitian menunjukkan siswa dengan kecerdasan logis matematis tinggi mampu mengidentifikasi semua indikator kemampuan literasi matematika dengan baik dan memiliki kemampuan literasi matematika tinggi. Hal berbeda untuk siswa dengan kecerdasan logis sedang dan rendah. Hasil identifikasi ini masih memungkinkan untuk ditindaklanjuti dengan suatu penelitian yang bersifat analisis.